Factors associated with decent work among psychiatrists: a cross-sectional study - Zhang, Xiaolan; Wang, Luoyan; Wu, Huaineng; Zhu, Simin; Jiang, Zhuojun; Xue, Bowen; Luo, Hong (Frontiers in Psychiatry, 2026)
ObjectiveThis study examined the current state of decent work among psychiatrists and explored factors associated with their perceptions of decent work.MethodsThis cross-sectional study used convenience sampling to recruit psychiatrists from eight hospitals in China. Data were collected online using the Self-Control Scale (SCS), the Career Adapt-Abilities Scale (CAAS), and the Decent Work Perception Scale (DWPS). A total of 517 valid responses were analyzed using SPSS 26.0. Correlation and regression analyses were conducted to identify factors associated with perceptions of decent work.ResultsCareer adaptability was positively associated with decent work (r = 0.534, p < 0.01), and self-control was also positively associated with decent work (r = 0.396, p < 0.01). Monthly income and professional title were significantly associated with decent work. Significant differences were found between psychiatrists earning less than 8,000 RMB and those earning 8,000–12,000 RMB (β = 0.178, p = 0.001), 12,000–20,000 RMB (β = 0.199, p = 0.001), and more than 20,000 RMB (β = 0.143, p = 0.005). A significant difference was also observed between resident physician and attending physician (β = -0.141, p = 0.010).ConclusionsIncome, professional title, self-control, and career adaptability were associated with psychiatrists’ perceptions of decent work. These findings may inform discussions on working conditions and contribute to efforts to support the sustainability of mental health services.